IMPLEMENTATION OF CHARACTER EDUCATION AT CIVIC EDUCATION IN 5.0 ERA ON FIFTH GRADE STATE ELEMENTARY EDUCATION VIDYA QASANA - Dewi Rakhmawati; Kus Eddy Sartono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2023)
The purpose of this research is to apply the character education model in the 5.0 era, find out the obstacles faced, and solutions that can be implemented in character education for fifth grade students at SDN Vidya Qasana. This research is a descriptive qualitative research case study method. The research subjects were school principals, fifth grade teachers, fifth grade students and gardeners. Sources of research data, researchers obtained from observation, interviews, and documentation. Data collection techniques through interview techniques, observation, and documentation. The validity of the data in this study were technical triangulation and peer discussion. Data analysis was carried out through the process of data reduction, data presentation and drawing conclusions. The results showed that (1) The application of character education in Civics learning in class V era 5.0 in K13 learning was carried out by the teacher by giving concrete examples to students, respecting differences, instilling discipline, disposing of waste according to its type and instilling social attitudes. (2) The results of implementing character education in Civics learning in class can be seen from the teaching and learning activities in class showing several attitudes, among others, mutual respect, submitting assignments on time, leaving class asking permission, not being noisy in class, and independent learning not depending on people other. (3) Obstacles and solutions to implementing character education at SDN Vidya Qasana. The obstacle is the lack of cooperation between the school and parents of students, students often ignore politeness, teachers do not respond to programs made by the principal who are still concerned with their personal interests. The solution to facing these obstacles is to establish communication between schools and parents of students, remind each other between students, and increase cooperation between teacher boards.